Estudo geológico e geofísico da falha de carnaubais, Bacia Potiguar-RN, e implicações neotectônicas - Caldas, Luciano Henrique de Oliveira (1998)
The segment of Carnaubais Fault located in the southeasthern portion of Guamaré Graben (Potiguar Basin) was studied. Several structures were detected and some of them strongly suggest that the last movements in Carnaubais Fault are of Neotectonic age. The study comprises an integrated interpretation of geologic, geomorphologic and geophysical data (gravimetry, magnetometry, resistivity, and self potential methods). According to the size of the studied areas, two approaches were used in this research. The first approach is of a regional nature and was conducted in an area, hereafter named Regional Area, having approximately 6,000 km2 and localized in the northern portion of Rio Grande do Norte state, around Macau city. The second approach comprises detailled studies of two small areas inside the Regional Area: the Camurupim and São Bento areas. Gravimetric and topographic data were used in the Regional Area. A separation into regional and residual components were conducted both on gravimetric and topographic data. The interpretation of the residual component of the gravimetric data allows a precise mapping of the borders of the Guamaré Graben. The regional component features of the topographic data are controlled by the pair of conjugate faults composed by the Carnaubais Fault (NE direction) and the Afonso Bezerra Fault (NW direction). On the other hand, the residual component of the topographic data shows that river valleis of NW direction are sharply interrupted where they intersect Carnaubais Fault. This fact is interpreted as an evidency that the last significant moviments occured in the Carnaubais Fault. Geologic, geomorphologic and geophysical data (magnetometry, resistivity, and self potential methods) were used in the Camurupim Area. The geologic mapping allows to identify five lithophacies unities. The first two unities (from base to top) were interpreted as composing a marine (or transitional) depositional sequency while the other were interpreted is composing a continental depositional sequence. The two sequences are clearly separated of an erosional discordance. The unities grouped in the marine sequence are composed by calcarenites (Unity A) and mudstones (Unity B). Unity A was deposited in a shalow plataform while Unity B, in a tidal flat. The unities grouped in the continental sequence are composed of conglomerate (Unity C) and sandstones (Unities D and E). Unities C and D are fluvial deposits while unity E is an eolian deposit. Unities A and B can be stratigraphycally correlated with Guamaré Formation. Unities C and D present three possible correlations. They may be correlated with Tibau Formation; or with Barreiras Formation; or with a clastic sediment deposit, commonly found in some rivers of Rio Grande do Norte state, and statigraphycally positioned above Barreiras Formation. Based on the decrease of the grain sizes from base to top both on unities C and D, it is proposed that these unities are correlated with the clastic sediment above mentioned. In this case, these unities would have, at least, Pleistocenic age. Finally, it is proposed that Unity E represent an eolian deposit that sufferred recent changes (at least in the Quaternary). The integrated interpretation of hydrographic, morphologic and geophysical data from Camurupim Area shows that Carnaubais Fault is locally composed by a system of several paralel subvertical faults. The fault presenting the larger vertical slip controls the valley of Camurupim river and separates the area in two blocks; in the nothern block the top of the Jandaira limestone is deeper than in the southern block. In addition, at least one of the faults in the northern block is cutting the whole sedimentary section. Because unities C , D, and/or E may be of Quaternary age, tectonic moviments possibly occured in Carnaubais Fault during this period. Detailled geologic mapping were conducted in beachrocks found in São Bento Area. This area is located at the intersection of the coast line with the Carnaubais Fault. The detected structures in the beachrocks are very similar to those caused by fragile deformations. The structures mapped in the beachrocks are consistent with a stress field with maximun compressional stress in E-W direction and extensional stress in the N-S direction. Since the Carnaubais Fault has a NE direction, it is optimally positioned to suffer tectonic movements under the action of such stress field. In addition, the shape of the coastal line appear to be controlled by the Carnaubais Fault. Furthemore, the observed structures in Camurupim Área are consistent with this stress field. These facts are interpreted as evidences that Carnaubais Fault and beachrocks suffered coupled tectonic movements. These moviments are of Neotectonic age because the beachrocks present ages less than 16,000 years